Smart Security : A Comprehensive Exploration of AI and IoT in Cybersecurity - Jyoti Bolannavar; Dr. Sumati Ramakrishna Gowda (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This paper investigates the transformative roles of Artificial Intelligence (AI) and the Internet of Things (IoT) in cybersecurity, especially as the complexity and connectivity of digital networks intensify. The rapid adoption of IoT devices in industries and homes alike has significantly broadened the cyber threat landscape, introducing countless points of vulnerability. Cybercriminals now target the vast and often unsecured data generated by IoT devices, exploiting weak access controls, outdated software, and inadequate encryption. In response, AI has become a critical tool in modern cybersecurity strategies, offering enhanced methods for threat detection, predictive analytics, and automated responses. AI-driven systems can proactively analyze patterns in network activity, detect anomalies, and anticipate future threats, all in real-time, providing a strong defence against increasingly sophisticated attacks. Additionally, AI facilitates automation in incident response, enabling immediate isolation or neutralization of threats before significant damage occurs. However, integrating IoT and AI in cybersecurity introduces new challenges, particularly concerning device interoperability, resource limitations in IoT devices, and privacy concerns due to the extensive data generated and processed. This paper explores these technologies in depth, examining their current applications, limitations, and the potential they hold for building smarter, more resilient cybersecurity frameworks in the future.